THE EFFECT OF COOPERATIVE LEARNING MODEL TYPE TEAMS GAME TOURNAMENT (TGT) ON LEARNING - Rahma Yani; Sahyar Sahyar (Jurnal Pendidikan Fisika, 2018)
This study aims to determine the effect of cooperative learning model type Teams Game Tournament (TGT) by using the monopoly media of conceptual knowlegde students in topic dynamic fluid. Method of this research is by using quasi experiment with one group post test pretest design. The research was conducted in SMA Negeri 1 Silangkitang Labuhan Batu Selatan Regency with cluster random class sampling technique and class selection was done randomly, the students of XI-1 class as the experimental class and XI-2 class as the control class were 30 students . The instrument used in this study is a multiple-choice test of conceptual knowledge with a total of 20 items and affective and skill observation sheets. Analysis using t-test at 5% significance level with prerequisite test of normality and homogeneity. From the research result, the average pretest of experiment class was 32,00 and the control class was 31,17 while the average posttest experiment class was 71,67 and the control class was 51,50. Hypothesis with t-test shows the result of physics conceptual knowledge with TGT type cooperative model by using monopoly media better than conventional learning. Based on the result, it can be concluded that there is influence of cooperative learning model type TGT to conceptual knowledge learning result.